Time to shine - Young, Jessica (Jessica E.); Vanderbemden, Marie (New York, NY : Scholastic Inc., 2021)
Winter has come to the Fairy Forest, and best friends Ruby, Iris, and Pip are eager to sample all the winter activities available like making snow fairies, sledding, and brewing snowflake tea--and building a simple greenhouse so Pip can start his garden despite the snow.
1.5
K-3
390L
Keywords: Fairies -- Juvenile fiction; Winter -- Juvenile fiction; Snow -- Juvenile fiction; Best friends -- Juvenile fiction; Fairies -- Fiction; Winter -- Fiction; Snow -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Fantasy; Readers (Elementary); Fantasy fiction